2018
DOI: 10.1016/j.cels.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Endogenous Replication Stress Causes ATR-Triggered Fluctuations in CDK2 Activity that Dynamically Adjust Global DNA Synthesis Rates

Abstract: Faithful DNA replication is challenged by stalling of replication forks during S phase. Replication stress is further increased in cancer cells or in response to genotoxic insults. Using live single-cell image analysis, we found that CDK2 activity fluctuates throughout an unperturbed S phase. We show that CDK2 fluctuations result from transient ATR signals triggered by stochastic replication stress events. In turn, fluctuating endogenous CDK2 activity causes corresponding decreases and increases in DNA synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 40 publications
(64 reference statements)
3
53
0
Order By: Relevance
“…Surprisingly, we discovered instead that cells re-entering the cell cycle from G0 are in fact, routinely and significantly underlicensed rendering them hypersensitive to replication stress compared to proliferating cells. This finding is consistent with a recent report that the first S phase experiences higher spontaneous replication stress, though the source of that endogenous stress was not identified (Daigh et al, 2018). We report here that MCM loading is slow in the first G1 phase and furthermore, that the first cell cycle has a severely compromised origin licensing checkpoint relative to the robust checkpoint in actively proliferating cells.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Surprisingly, we discovered instead that cells re-entering the cell cycle from G0 are in fact, routinely and significantly underlicensed rendering them hypersensitive to replication stress compared to proliferating cells. This finding is consistent with a recent report that the first S phase experiences higher spontaneous replication stress, though the source of that endogenous stress was not identified (Daigh et al, 2018). We report here that MCM loading is slow in the first G1 phase and furthermore, that the first cell cycle has a severely compromised origin licensing checkpoint relative to the robust checkpoint in actively proliferating cells.…”
Section: Introductionsupporting
confidence: 92%
“…Previous analysis by Daigh et al indicated that cells released from G0 had increased endogenous replication stress in the first S phase compared to actively proliferating cells. This stress was detected as mid-S phase fluctuations in CDK activity plus markers of the replication stress response signaling pathway (Daigh et al, 2018). Our findings here suggests a molecular mechanism by which that replication stress is generated.…”
Section: Discussionmentioning
confidence: 54%
“…Rather unexpectedly, however, under unperturbed growth conditions, KR clones showed lower proliferation rates ( Figure S1D), coupled with a reduced proportion of cells undergoing DNA synthesis as measured by EdU incorporation ( Figure S1E). As this pattern was reminiscent of cells experiencing increased levels of endogenous replication stress (Daigh et al, 2018), we next investigated expression of DNA damage markers. We observed that, in the absence of any exogenous DNA damage treatment, KR cells showed increased levels of Chk2 phosphorylation ( Figure 1D) and 53BP1 chromatin foci ( Figure 1E-F), indicating DSB accumulation.…”
Section: Endogenous Replication Stress and Increased Fork Speed In Pcmentioning
confidence: 99%
“…The activity ratio increases from approximately 0.5 at basal, to 1 at the G1/S transition, and to 1.5 when cells enter mitosis. We note that the reporter detects primarily cyclin E-CDK2 activity in G1 since there is minimal cyclin A protein or CDK1 activity in G1 12,31,33,34 . Starting live-cell imaging at the time of mitogen release to determine an activity baseline, we found that a portion of CDK4/6 inhibitortreated cells indeed upregulated cyclin E/A-CDK activity ( Fig.…”
Section: Cells Without Cdk4/6 Activity Exhibit Slowed and Fluctuatingmentioning
confidence: 90%
“…In cell-cycle control, irreversible steps are necessary for maintaining the proper order of cell-cycle phases [42][43][44] , and without EMI1-mediated APC/C CDH1 inactivation, genome integrity is compromised 11,45,46 . As cell can temporally inactivate cyclin E/A-CDK in response to DNA damage, a role of EMI1 is likely to prevent inadvertent APC/C CDH1 reactivation in S phase, where endogenous DNA damage can suppress cyclin E/A-CDK activity 34 . In CDK4/6-inhibited cells, E2F-mediated EMI1 transcription is delayed similar to that of E2F1 (Extended Data Fig.…”
Section: Apc/c Cdh1 Inactivation Is Reversible Until Rb Inactivation mentioning
confidence: 99%